Neonatal sepsis: Risk factors, clinical and bacteriological profile, and antibiotic sensitivity - Sethi, Anitha B; Srigade, Vedavyasa; Dharmateja, Guntur (Indian Journal of Child Health, 2018)
Background: Neonatal sepsis (NS) is a cause of very high morbidity and mortality. Reviews of bacterial spectrum and antimicrobial susceptibility help to treat NS and to develop strategies to lower neonatal mortality. Objectives: The objectives were to study organisms causing NS, their antimicrobial susceptibility pattern, predisposing factors of NS, and the presentations of NS. Methods: This prospective study was done for 1 year from August 2016 to July 2017 at a tertiary care hospital, Hyderabad with C-reactive protein (CRP), aerobic blood cultures, and sensitivities in 300 neonates with clinical sepsis. Risk factors for NS and clinical features were recorded. Significances for sex, gestational age, birth weight, and age of onset of sepsis differences were assessed. Results: Male to female ratio was 1.65:1, 39% were preterm, 40% were